Structure Prediction and Ultrasonic Assisted Synthesis of Coordination Compound Cadmium (II) Bromide with N,N’-diethylthiourea Ligand - Susanti, Yuni; Fariati, Fariati; Effendy, Effendy; Azizah, Yulyani Nur (Jurnal Kimia Valensi, 2023)
Cadmium (II) halides with N,N'-diethylthiourea (detu) ligands at a stoichiometry of 1: 2 tend to form molecular complexes [Cd(detu)2X2] with a distorted tetrahedral geometry at the central atom. Generally, these complex compounds are prepared by the conventional method of reflux for 4 hour. The use of ultrasonic waves for complex synthesis can be an alternative to make the reaction time more efficient and environmentally friendly. The aim of this study was to synthesize and characterize complex compounds from CdBr2 and detu ligands using the ultrasonication method that have not previously reported. The synthesis of complex compounds was carried out by reacting CdBr2 and detu (1:2) in methanol solvent. In the synthesized compounds, a melting point test, electrical conductivity test, Fourier Transform Infrared (FTIR), Scanning Electron Microscope-Energy Dispersive Xray (SEM-EDX), qualitative test of bromide ion and calculation of free energy using Spartan'14 software were carried out for the complex structure prediction. The complex compound resulted has colorless needle crystals with a melting point of 93-94°C. The results of the EDX analysis provide the empirical formula C10H24CdBr2N4S2. The electrical conductivity test data and the bromide ion qualitative test proved that the synthesized complex compound was a molecular complex compound with the molecular formula [Cd(detu)2Br2]. The complex compound has two possible structures, namely a distorted tetrahedral and a square planar. Free energy calculations showed that complex compounds with a distorted tetrahedral structure and a square  planar have free energies of -527.5574 kJ/mol and -408.7424 kJ/mol, respectively.